Manifestaciones clínicas de presentación de Neurocisticercosis - Villalobos-Perozo Rafael (Kasmera, 2003)
Abstract: Neurocysticercosis is the most commonst parasitic disease in the Human Nervous System (HNS). It is a zoonosis with high prevalence in underdeveloped countries where bad environmental conditions and cohabitation with pigs favor its development. Although its prevalence in Venezuela is unknown, sporadic cases are presented in regional hospitals. In this descriptive, retrospective research, the clinical manifestations of its presentation of 15 patients are reported. Patients were treated in the Instituto Autonomous Maracaibo Hospital Institute, Zulia state over the last 10 years, and were diagnosed by Computarized Axial Tomography (CAT) or Magnetic Resonance (MR). Ten (10) patients were males and five (5) were females. The age group most affected was from 30 to 44 years of age (43%). The most frequent clinical manifestations were: headaches (27%), seizures (20%), blurred vision (13%), nausea and vomiting (13%), dizziness (13%), loss of conscience (7%) and loss of the muscle strength (7%). These last clinic manifestations mentioned are uncommon in medical reports about Neurocysticercosis, which makes it a necessary consideration when differential diagnosis is made.